Wellbeing education increases skills and knowledge among tertiary students in the agricultural sector: insights from a mixed methods study - Winder L; Stanley-Clarke N; Maris R; Hay A; Knook J (Taylor and Francis Group, 2024)
Purpose The agricultural sector is facing a myriad of financial, environmental, social, and cultural challenges which affect the mental health of those working on-farm. This study focused on a tertiary education programme designed to increase recognition of mental health issues and convey strategies to address these. Methodology To identify the effect of such a programme, and which aspects contribute to that effect, this paper applied a mixed methods approach. Quantitative propensity score matching was used to identify changes in knowledge and skills, and qualitative surveys were conducted to explore the wellbeing of students and to identify aspects of the programme contributing to change. Findings Students report an increase in (i) ability recognising signs of poor mental health in self and others; (ii) confidence talking about their own and others’ mental health; and (iii) knowing how to access mental health support services. Programme aspects contributing to this effect are peer-to-peer education and building on existing knowledge. Practical implications This paper addresses a gap in the literature by providing insights into programme aspects that lead to successful delivery. Theoretical implications This study reports on the evaluation of a tertiary education programme and provides valuable insights into whether such programmes can contribute to increased knowledge on wellbeing. Originality This research describes and analyses the effectiveness of a mental health promotion programme aimed at young adults which is rare in the literature.
Keywords: Evaluation; higher education; mental health; mixed methods; rural; wellbeing